TINJAUAN YURIDIS PELAKSANAAN REHABILITASI BAGI PENYALAH GUNA NARKOTIKA BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Mitarji; Indah Sari (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN, 2025)
This study aims to explain: About the Legal Review of the Implementation of Rehabilitation for Narcotics Abusers Based on Law Number 35 of 2009 concerning Narcotics, as a positive law in Indonesia in efforts to overcome and rehabilitate narcotics abusers. In Article 54 of Law Number 35 of 2009 concerning Narcotics it is explained that: